Running Programs for Wrestling - Lee, R.
Wrestling is a very tough sport. You must be able to have explosive power for a take down. You must also be able to maintain that power for about 5 minutes. What you need to do is improve your anaerobic conditioning level. Many wrestlers make the mistake of going for long slow three-mile runs to get in shape. This is not specific to wrestling. In fact it training for endurance may actually decrease your power. You need to train you body to recruit fast-twitch fibers and buffer lactic acid that accumulates. The way to do this is through anaerobic conditioning. Anaerobic basically means without oxygen. It involves higher intensity work with less recovery. Interval sprinting is a great way to improve your anaerobic conditioning level. Try using rest rates of 1:2 - 1:3. For example, if you do a 15-second sprint, rest for 30-45 seconds then do another one. Here are some sample running workouts that will improve your anaerobic fitness: 1.Always perform a warm-up first (5 minute run or jump rope and stretch) 2.Cool down after with 10 minute light jog/walk and stretch